2017
DOI: 10.1007/s00384-017-2858-9
|View full text |Cite
|
Sign up to set email alerts
|

Should we offer ventral rectopexy to patients with recurrent external rectal prolapse?

Abstract: VR is a better option for patients undergoing primary rectal prolapse repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
3
14
1
Order By: Relevance
“…Previous VMR induces adhesion formation to the pelvic area, and it could be expected that this hampers reoperations. In light of this, our study showed a reasonably low complication rate of 23.3%, which is in line with the results of Gurland et al [15], who reported a complication rate of 19.4%. Brunner et al [16] had a lower complication rate (13.3%) in their study.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Previous VMR induces adhesion formation to the pelvic area, and it could be expected that this hampers reoperations. In light of this, our study showed a reasonably low complication rate of 23.3%, which is in line with the results of Gurland et al [15], who reported a complication rate of 19.4%. Brunner et al [16] had a lower complication rate (13.3%) in their study.…”
Section: Discussionsupporting
confidence: 93%
“…Its effect on improving QoL, symptom changes for the better and less postoperative pelvic pain were more likely in patients with ERP than in IRP patients. There are only two previous publications reporting the results of LVMR or RVMR performed as revisional surgery [15,16]. They differ significantly from our study, since the primary operations in these studies varied, including perineal operations such as Altemeier and Delorme procedures.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…This was studied in a prospective cohort study looking at 108 patients who underwent VR. 17 Prolapse recurrence rates were reported at 1.4, 6.9, and 9.7% for primary repairs and at 13.9, 25, and 25% for recurrent prolapse procedures at 1, 3, and 5 years, respectively. Time to recurrence was much shorter for those undergoing VR for recurrent prolapse.…”
mentioning
confidence: 91%